Induction of Apoptosis in Endometrial Cancer (Ishikawa) Cells by Pogostemon cablin Aqueous Extract (PCAE) - Ching-Chou Tsai (International Journal of Molecular Sciences, 2015)
Pogostemon cablin (PC) is a traditional herbal medicine used in the treatment of the common cold, nausea, diarrhea, and even for headaches and fever. However, the mechanisms underlying the anti-proliferative activity of PC in endometrial cancer (EC) cells have yet to be fully elucidated. This study investigated the anticancer effects of an aqueous extract of Pogostemon cablin (PCAE), specifically induced apoptosis in EC (Ishikawa) cells. Proliferation of EC cells following exposure to PCAE was assessed by an MTT assay. DNA content and the induction of cell cycle apoptosis were analyzed by flow cytometry (FACS Calibur). Protein caspase-3 and, -9 as well as AIF were investigated using Western blot. Our results demonstrate growth inhibition of Ishikawa cells by PCAE. Furthermore, caspase-3 activity caused PCAE-treated cell lines to accumulate in apoptosis. Gene expression profiling (GEP) results further suggest that, in addition to its known effects with regard to EC prevention, PCAE may also exert antitumor activity on established EC cells. Many previous studies have identified the chemo-preventive effects of natural plant materials and the potential role of these materials in chemotherapy. This current study used human EC Ishikawa cells to investigate the anti-tumor effects of PCAE in EC cells. Our results demonstrate that PCAE inhibits the growth of cancer cells and induces apoptosis, which suggests the potential applicability of PCAE as an antitumor agent.